Robotizing to Compete? Firm-level Evidence - Paulo Bastos; Lisandra Flach; Klaus Keller (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We investigate the impact of product market competition on firms' automation investments. We use a rich combination of micro-data on Portuguese exporters and exploit a novel source of variation in the degree of competition they face – a tariff liberalization between the European Union and Central and Eastern European countries in the 1990s. We find that firms facing greater competition in export markets tend to reduce investments in automation technologies. These average negative effects are driven by the least productive firms, while the most efficient exporters in industries that are more prone to automation tend to robotize in order to compete. These findings suggest that an increase in the degree of product market competition widens disparities between firms.
Keywords: D22; F16; J23; L25; O33; 330; automation; product market competition; firm heterogeneity; trade liberalization; workers; multi-product firms